Americanaland : Where Country & Western Met Rock 'n' Roll - Milward, John (Book collections on Project MUSE., 2021)
A musical genre forever outside the lines With a claim on artists from Jimmie Rodgers to Jason Isbell, Americana can be hard to define, but you know it when you hear it. John Milward's 'Americanaland' is filled with the enduring performers and vivid stories that are at the heart of Americana.